Effects of glucagon, dibutyryl cyclic 3′,5′-adenosine monophosphate, and theophylline on calcitonin secretion in vitro - Norman H. Bell (The Journal of Clinical Investigation, 1970)
The secretion of calcitonin by slices of porcine thyroid glands has been investigated. Calcitonin in the incubation medium was determined by radioimmunoassay. Secretion of calcitonin was diminished when calcium or magnesium was omitted and was increased stepwise as the concentration of calcium or magnesium in the incubation medium was increased. Calcitonin secretion was augmented substantially when either the quantity of thyroid tissue or volume of incubation medium was increased. Secretion of calcitonin was stimulated by glucagon, theophylline, and dibutyryl cyclic 3′,5′-adenosine monophosphate. It is concluded that calcitonin secretion is regulated by the concentration of calcium and magnesium, that secretion may be inhibited by calcitonin or a precursor and that secretion can be stimulated by increasing the concentration of cyclic 3′,5′-adenosine monophosphate in the parafollicular cells of the thyroid gland.